Strategi Career Mapping untuk Meningkatkan Kesiapan Kerja Siswa Kelas XII SMK NU 01 Kendal – Jawa Tengah - Abdul Khafid; Amalia Rosada; Khoirul Anam; Bambang Wahyudi; Ripan Ripan; M.Neneng Sofiyanti (Jurnal Kabar Masyarakat, 2026)
Graduates of Vocational High Schools (SMK) are expected to possess a high level of work readiness to compete effectively in the industrial sector. A persistent issue is students' limited ability to plan their careers systematically, which results in suboptimal readiness to enter the workforce. This Community Service (PkM) activity aimed to enhance students' understanding of career mapping strategies as a foundation for developing career plans. The activity was conducted on April 24, 2026, at SMK NU 01 Kendal, utilizing a combination of lectures, discussions, practical career map creation, simulations, and evaluations via pre-tests and post-tests. Forty students participated in the event. Evaluation results showed an increase in the average score from 61.8 in the pre-test to 86.4 in the post-test. Furthermore, participants were able to construct career maps aligned with their interests, competencies, and professional goals. The activity demonstrates that career mapping training can improve students' understanding of career planning and strengthen their work readiness.